Valuation of Hyundai Motor Company - Lee, Taehyun; Ali, Tanweer; Sieber, Patrik, 1977-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2025)
This thesis conducts a financial valuation of Hyundai Motor Company, a leading global player in the automotive industry. Using methodologies such as Discounted Cash Flow (DCF) analysis and sensitivity analysis, the study aims to determine the intrinsic value of Hyundai Motor Company by evaluating its financial performance and strategic initiatives. With its extensive product portfolio and innovative investments in electric vehicles and hydrogen fuel cell technologies, Hyundai has solidified its position as a pioneer in sustainable mobility solutions. The analysis delves into Hyundai's financial statements, assessing key metrics such as revenue growth, operating profit, and capital expenditures. Additionally, sensitivity analysis is employed to evaluate the impact of changes in key variables, such as Weighted Average Cost of Capital (WACC) and growth rates, on Hyundai’s valuation. By providing a comprehensive assessment of Hyundai Motor Company's financial stability and future prospects, this thesis offers valuable insights into valuation practices within the automotive sector, highlighting investment opportunities and potential risks in a rapidly evolving industry.
Vedoucí práce: Tanweer Ali
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: bachelor of business administration [obor bakal. práce]; bakalářské práce; bachelor's theses